Specific genetic aberrations of parathyroid in Chinese patients with tertiary hyperparathyroidism using whole-exome sequencing - Li, Lei; Sheng, Qixuan; Zeng, Huajin; Li, Wei; Wang, Qiang; Ma, Guanjun; Xu, Xinyun; Qiu, Ming; Zhang, Wei; Shan, Chengxiang (Frontiers in Endocrinology, 2023)
Background Tertiary hyperparathyroidism (THPT) is a peculiar subtype of hyperparathyroidism that usually develops from chronic kidney disease (CKD) and persists even after kidney transplantation. Unlike its precursor, secondary hyperparathyroidism (SHPT), THPT is characterized by uncontrolled high levels of calcium in the blood, which suggests the monoclonal or oligoclonal proliferation of parathyroid cells. However, the molecular abnormalities leading to THPT have not yet been fully understood. Methods In this study, we analyzed DNA samples from hyperplastic parathyroid and corresponding blood cells of 11 patients with THPT using whole-exome sequencing (WES). We identified somatic single nucleotide variants (SNV) and insertions or deletions variants (INDEL) and performed driver mutation analysis, KEGG pathway, and GO functional enrichment analysis. To confirm the impact of selected driver mutated genes, we also tested their expression level in these samples using qRT-PCR. Results Following quality control and mutation filtering, we identified 17,401 mutations, comprising 6690 missense variants, 3078 frameshift variants, 2005 stop-gained variants, and 1630 synonymous variants. Copy number variants (CNV) analysis showed that chromosome 22 copy number deletion was frequently observed in 6 samples. Driver mutation analysis identified 179 statistically significant mutated genes, including recurrent missense mutations on TBX20, ATAD5, ZNF669, and NOX3 genes in 3 different patients. KEGG pathway analysis revealed two enriched pathways: non-homologous end-joining and cell cycle, with a sole gene, PRKDC, involved. GO analysis demonstrated significant enrichment of various cellular components and cytobiological processes associated with four genes, including GO items of positive regulation of developmental growth, protein ubiquitination, and positive regulation of the apoptotic process. Compared to blood samples, THPT samples exhibited lower expression levels of PRKDC, TBX20, ATAD5, and NOX3 genes. THPT samples with exon mutations had relatively lower expression levels of PRKDC, TBX20, and NOX3 genes compared to those without mutations, although the difference was not statistically significant. Conclusion This study provides a comprehensive landscape of the genetic characteristics of hyperplastic parathyroids in THPT, highlighting the involvement of multiple genes and pathways in the development and progression of this disease. The dominant mutations identified in our study depicted new insights into the pathogenesis and molecular characteristics of THPT.